Reflection of the Concept of the Meaning of Life on Mental Health In The Lyrics of Teramini's Songs - Nourma Ayu Safithri Purnomo. (LPPM Universitas Advent Indonesia, 2026)
Mental health is an interesting topic to discuss in the digital age. Many media outlets discuss the concept of mental health, one of which is through literary works in the form of music. Music, which consists of various song lyrics, can be a medium of expression for conveying messages about an individual's psychological condition. One of the variables that plays an important role in the realization of mental health is the meaning of life and song titles that describe the concept of meaning of life, such as Teramini by Ghea Indrawari. This study aims to deeply reflect on the concept of meaning of life in the lyrics of